2017
DOI: 10.3727/096504016x14791715355957
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated miR-9-3p Promotes Cell Growth and Inhibits Apoptosis in Medullary Thyroid Carcinoma by Targeting BLCAP

Abstract: Medullary thyroid carcinoma (MTC) is a neuroendocrine cancer derived from parafollicular C cells in the thyroid gland. It has great interest as a research focus because of its unusual genetic, clinical, and prognostic characteristics. However, the pathogenesis in MTC is not completely clear. We investigated the role of miR-9-3p and bladder cancer-associated protein (BLCAP) in MTC TT cells. First, miR-9-3p expression was upregulated in human MTC tissues and TT cells and compared to the control by RT-PCR. Flow c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…Many miRNAs identified as dysregulated in the present study have also been reported as altered in other cancer types, including breast cancer (miR‐374b‐5p, miR‐429, miR‐200b‐5p, miR‐200b‐3p, miR‐187‐3p, miR‐196a‐5p, miR‐183‐5p, miR‐21‐5p, and miR‐182‐5p); gastric cancer (miR‐374b‐5p, miR‐200c‐3p, miR‐18b‐5p, miR‐196a‐5p, miR‐21‐5p, and miR‐20a‐3p); ovarian cancer (miR‐141‐5p, miR‐182‐5p, miR‐483‐3p, and miR‐200c‐3p); hepatocellular carcinoma (miR‐135a‐5p, miR‐187‐3p, miR‐148a‐5p, miR‐200a‐3p, and miR‐9‐3p); colorectal cancer (miR‐9‐3p, miR‐135a‐5p, miR‐200c‐3p, miR‐200b‐3p, and miR‐182‐5p); thyroid cancer (miR‐7‐5p and miR‐9‐3p); lung cancer (miR‐200b‐5p, miR‐200b‐3p, miR‐9‐5p, miR‐200a‐3p, and miR‐21‐5p); pancreatic cancer (miR‐200b‐3p, miR‐483‐3p, and miR‐183‐5p); chronic lymphocytic leukemia (miR‐4521, miR‐7‐5p, and miR‐182‐5p); Hodgkin lymphoma (miR‐876‐5p); cervical cancer (miR‐429); head and neck squamous cell carcinoma (miR‐200b‐5p); and bladder cancer (miR‐148a‐3p) …”
Section: Discussionsupporting
confidence: 65%
“…Many miRNAs identified as dysregulated in the present study have also been reported as altered in other cancer types, including breast cancer (miR‐374b‐5p, miR‐429, miR‐200b‐5p, miR‐200b‐3p, miR‐187‐3p, miR‐196a‐5p, miR‐183‐5p, miR‐21‐5p, and miR‐182‐5p); gastric cancer (miR‐374b‐5p, miR‐200c‐3p, miR‐18b‐5p, miR‐196a‐5p, miR‐21‐5p, and miR‐20a‐3p); ovarian cancer (miR‐141‐5p, miR‐182‐5p, miR‐483‐3p, and miR‐200c‐3p); hepatocellular carcinoma (miR‐135a‐5p, miR‐187‐3p, miR‐148a‐5p, miR‐200a‐3p, and miR‐9‐3p); colorectal cancer (miR‐9‐3p, miR‐135a‐5p, miR‐200c‐3p, miR‐200b‐3p, and miR‐182‐5p); thyroid cancer (miR‐7‐5p and miR‐9‐3p); lung cancer (miR‐200b‐5p, miR‐200b‐3p, miR‐9‐5p, miR‐200a‐3p, and miR‐21‐5p); pancreatic cancer (miR‐200b‐3p, miR‐483‐3p, and miR‐183‐5p); chronic lymphocytic leukemia (miR‐4521, miR‐7‐5p, and miR‐182‐5p); Hodgkin lymphoma (miR‐876‐5p); cervical cancer (miR‐429); head and neck squamous cell carcinoma (miR‐200b‐5p); and bladder cancer (miR‐148a‐3p) …”
Section: Discussionsupporting
confidence: 65%
“…Furthermore, among target genes of miR-339-5p, as is shown in Figure 4B,C, BLCAP transcript level was significantly correlated with MALAT1 mRNA level and expression alterations of MALAT1, miR-339-5p and BLCAP in breast carcinoma were demonstrated from TCGA at cBioportal. In addition, it has been reported that BLCAP can be regulated by miR-9-3p to promote cell growth and inhibit apoptosis in medullary thyroid carcinoma [14], and there was only one potential complementary site for miR-339-5p in the 3′UTR of BLCAP mRNA. Therefore, we focused on BLCAP as the primary candidate.…”
Section: Resultsmentioning
confidence: 99%
“…MiRNAs are involved in many biological processes, including cell proliferation, differentiation, and apoptosis, via the targeting of gene mRNA 3′UTR. Abnormal expression of certain miRNAs was observed in some cancers compared to normal tissues, such as endometrial carcinoma (Bao et al, 2013), breast cancer (Rhodes et al, 2015), ovarian cancer (Vilming Elgaaen et al, 2014), gastric cancer (Li et al, 2015), hepatocellular carcinoma (Yao et al, 2016), Hodgkin's lymphoma (Paydas et al, 2016), thyroid cancer (Chen et al, 2017), acute promyelocytic leukemia (Garzon et al, 2007), bladder cancer (Wang et al, 2016), and chronic lymphoblastic leukemia (Calin et al, 2005). Various miRNAs may act as oncogenes or tumor suppressor genes according to their roles in tumorigenesis (Boufraqech, Klubo-Gwiezdzinska, & Kebebew, 2016).…”
Section: Discussionmentioning
confidence: 99%